2008
DOI: 10.1007/s11251-008-9051-z
|View full text |Cite
|
Sign up to set email alerts
|

Assisting self-explanation prompts are more effective than open prompts when learning with multiple representations

Abstract: Learning with multiple representations is usually employed in order to foster understanding. However, it also imposes high demands on the learners and often does not lead to the expected results, especially because the learners do not integrate the different representations. Thus, it is necessary to support the learners' self-explanation activity, which concerns the integration and understanding of multiple representations. In the present experiment, we employed multi-representational worked-out examples and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 186 publications
(122 citation statements)
references
References 37 publications
6
114
0
2
Order By: Relevance
“…Learners tend to use journals to report descriptive accounts of events with no deeper reflection of underlying meaning Hargreaves 2004;Minott 2008;O'Connell and Dyment 2004;Richardson and Maltby 1995;Ryan 2013;Wessel and Larin 2006). Learners need tools and scaffolds to report and reflect on their experiences (Berthold et al 2009;Hübner et al 2010;Kicken et al 2009). Prompts have been studied as scaffolds that aim to structure learners' reflections (Nückles et al 2009).…”
Section: Scaffolding For Reflectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Learners tend to use journals to report descriptive accounts of events with no deeper reflection of underlying meaning Hargreaves 2004;Minott 2008;O'Connell and Dyment 2004;Richardson and Maltby 1995;Ryan 2013;Wessel and Larin 2006). Learners need tools and scaffolds to report and reflect on their experiences (Berthold et al 2009;Hübner et al 2010;Kicken et al 2009). Prompts have been studied as scaffolds that aim to structure learners' reflections (Nückles et al 2009).…”
Section: Scaffolding For Reflectionmentioning
confidence: 99%
“…Among others, they contribute to help learner connecting theory and practice , to foster deep or strategic learning (Entwistle 2000), and to promote self-regulated learning (Chang et al 2015;Tanner et al 2000). However, learning journals need scaffolds to be efficient for learning (Berthold et al 2009;Eraut 2007;Hüb-ner et al 2010;Kicken et al 2009). Thus, the open question is not anymore if using learning journals can be beneficial but if specific ways of using learning journals have a larger impact on student learning than others.…”
mentioning
confidence: 99%
“…All students were native speakers of German. Pre-studies had indicated that undergraduates generally had problems understanding and applying urn models without training (see also Berthold, Eysink, & Renkl, 2009). …”
Section: Participantsmentioning
confidence: 99%
“…In order to facilitate learning, several different and very specific prompts may be employed that focus on problem-solving [15] general instruction [5], self-explanation [16], or encouraging recall, reasoning, or observation [5]. Prompts can serve multiple functions and can focus on cognitive learning processes, metacognitive self-regulation, and resource management [17].…”
Section: Prompting For Improved Self-regulationmentioning
confidence: 99%